Anti-inflammatory treatment after cataract surgery in Sweden: changes in prescribing patterns from 2010 to 2017. Issue 1 (23rd March 2021) - Samadi, Behrad; Lundstrom, Mats; Zetterberg, Madeleine; Nilsson, Ingela; Montan, Per; Behndig, Anders; Kugelberg, Maria
Abstract : Aims: To investigate changes in the prescribing patterns of postoperative eye drops following cataract surgery in Sweden from 2010 to 2017. Methods: Data from cataract procedures registered in the National Cataract Register during the month of March from 2010 to 2017 were record linked and sent to the Swedish Prescribed Drug Register, which allowed us to determine which eye drops the patients had obtained from 3 months presurgery to 2 weeks post surgery. Results: During the 8-year study period, 54 889 surgeries were registered. Combination treatment with steroid and non-steroidal anti-inflammatory drug (NSAID) eye drops increased from 12% in 2010 to 60% in 2017 (p<0.001) while monotherapy with steroids decreased from 71% in 2010 to 26% in 2017 (p<0.001). Monotherapy with NSAIDs after surgery was fairly stable, at 17% in 2010 and 13% in 2017 (p<0.001). Combination treatment was more frequent in patients with diabetic retinopathy (p<0.001) or age-related macular degeneration (p<0.001), while monotherapy with steroids was more frequent in patients with glaucoma (p<0.001). The proportion of monotherapy or combination therapy varied widely between ophthalmic clinics. The prescription of antibiotic eye drops after surgery also varied greatly between clinics, from 0% to 63%, with a national average of 4.9%. Conclusion: There is a change in the prescription pattern of anti-inflammatory eye drops after cataract surgery in Sweden, with less monotherapy and an increasing proportion of patients receiving a combination of steroid and NSAID eye drops.